Mobile Learning in Medical Coding Course: Intention to Use MedCoS - Nor Intan Shamimi Abdul Aziz; Dilla Syadia Ab Latiff; Siti Noorsuriani Maon; Annurizal Anuar (International Journal of Online and Biomedical Engineering (iJOE), 2023)
Medical coding is a subject in which students must assign proper ICD-10 codes to patients’ diagnoses as reported in the coding exercises. However, due to students’ inadequate knowledge, incorrect codes are assigned to the cases, leading to coding errors. Thus, creating Medical Coding Simulation (MedCoS) is to help students strengthen their motor and technical abilities in challenging scenarios. The purpose of this study is to predict students’ intention to use MedCoS based on attitudes (AT), subjective norms (SN), and perceived behavioral control (PBC). To meet the objective, SPSS was used to conduct descriptive, reliability, and multiple regression analyses. This study includes students in Semester five and six who have attended both courses. Majority respondents were female (89.9%, n=116) and aged between 23 and 24 years old (90.2%, n=102). Results showed that attitudes and perceived behavioral predicted the intention to use MedCos among the students. The significant outcome allows MedCoS to plan the next stage of the application’s development with the goal of achieving the desired improvement in course performance.